An Extension of DNA Splicing Systems - Yuhani, Yusof; Nor Haniza, Sarmin; Mazri, Mahmud; T., Elizabeth Goode; Fong, Wan Heng (2011)
The first mathematical model of a splicing system that was analyzed in the framework of Formal Language Theory was developed in 1987 by Head. This model consists of a finite alphabet, a finite set of initial strings over the alphabet, and a finite set of rules that act upon the strings by iterated cutting and pasting, generating new strings. In this paper, a new notation for writing rules in a splicing system and a new extension of splicing systems is introduced in order to make the biological process transparent. These are called Yusof-Goode rules, and they are associated with Yusof-Goode splicing systems. Four different classes of splicing systems are discussed: null-context, uniform, simple and SkH systems. Also, counterexamples are given to illustrate relationships between these splicing system classes.